ANALISIS PEMIDANAAN TERHADAP TINDAK PIDANA PERTAMBANGAN BATUBARA TANPA IZIN USAHA PERTAMBANGAN STUDI KASUS DI KUTAI - Endrico Putri, Victoria Sherly (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The development of mining crimes without mining business licenses at this time still occurs a lot, even though it has been regulated in Law Number 4 of 2009 concerning Mineral and Coal Mining, but in reality, convictions against perpetrators of mining business crimes without permits still deviate from Law Number 4 of 2009 concerning Mineral and Coal Mining, and not a few also the perpetrators of mining business without permission are given a light punishment not in accordance with the existing regulations even exempt. If this is kept on continuously, then mining business activities without permits will become more widespread and this will greatly harm the country and damage the environment. As for that being a problem formulation in the writing of this are how the mechanism of mining business activities in the mining of PT Utama Kawan Energi and whether the punishment in Case Decision Number 153 K / PID.SUS / 2016 has been in accordance with Law Number 4 of 2009 concerning Minerals and Coal Mining. And in this paper, using normative legal research methods (literature) to get the results of research on matters that are the problem in this writing, namely PT Utama Kawan Energi in conducting mining business activities not in accordance with what is regulated in Law Number 4 In 2009 about Minerals and Coal and the Judges even though they had punished him according to the laws and regulations, however, in imposing judgments the judges gave very light punishments, it should be based on the objective theory of absolute punishment, the Judges should give maximum punishment because what the defendant caused was very large.